Control interno de inventario en la ferretería Gaibor en el año 2020-2021 - Cabrera Carriel, Mariuxi Jamilet (2022)
The internal control of inventories constitutes one of the fundamental pillars within a company, since an adequate management of the same will contribute to the improvement of the administration of the finances to avoid economic losses that could occur due to high financial costs originated by the keeping excessive amounts of stock that do not have much outlet within the business. This case study seeks to optimize and correct the fragile inventory management system carried out by the company “GAIBOR” located in the city of Babahoyo. Endless economic repercussions were caused by the COVID-19 pandemic caused by the SarsCov2 virus, specially in the SME sector, and the company “GAIBOR” could not be the exception; so that consequences were the starting point for the progressive decay within the company with regard to internal inventory control. The main objective of this study is to emphasize the importance of good management of inventory control and the benefits that would be obtained from it within the company. Finally, after the evaluations and interviews carried out in the company, a poor inventory control was evidenced; for this reason, the necessary recommendations were provided to the owner and manager of the company to improve said registration system in a timely manner and, in this way, achieve the optimization of the financial management system of the company “GAIBOR”.